9 Anorectal Abscess and Fistula-In-Ano (Gordon and Nivatvongs’ Principles and Practice of Surgery for the Colon, Rectum, and Anus, 2019)
A majority of abscesses are of nonspecific cryptoglandular origin but may also be due to a variety of processes, which are primarily inflammatory or traumatic. A fistula typically begins in the middle of the anal canal at the level of the crypts and extends downward to the anal verge. Penetration through the external sphincter will lead to an abscess into the ischioanal fossa, while upward extension by way of the intersphincteric plane will course along the rectal wall or penetrate beyond the rectum. High upward extension can enter the true pelvis. The most common presenting symptoms for anorectal abscess are pain and swelling. Presentation of fistula-in-ano may be subtle, but most patients will give a history of prior abscess or anorectal procedures. This chapter focuses on etiology and pathology, avenues of extension, diagnosis, investigations, treatment, and complications related to anorectal abscess and fistula-in-ano.
Keywords: anorectal abscess; fistula-in-ano; anal fistula; etiology; pathogenesis; diagnosis; anoscopy; proctoscopy; treatment; fistulotomy